2010
DOI: 10.1186/1472-6831-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Farsi version of the Early Childhood Oral Health Impact Scale (F-ECOHIS)

Abstract: BackgroundThe Early Childhood Oral Health Impact Scale (ECOHIS) has recently been developed to assess oral health-related quality of life (OHRQoL) of pre-school children in English speaking communities. This study aimed to translate the ECOHIS into Farsi and test its psychometric properties for use on 2- to 5-year-old children of Farsi speaking Iranian families.MethodsEHOHIS questionnaire was translated into Farsi using a standardized forward-backward linguistic translation method. Its face and content validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
83
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(117 citation statements)
references
References 22 publications
19
83
4
3
Order By: Relevance
“…However, in the study conducted by Jabarifar et al, and the study conducted by Macintyre et al female participants had higher scores than males (9,21). The reason for this difference was the type of questionnaire and the age group of participants.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…However, in the study conducted by Jabarifar et al, and the study conducted by Macintyre et al female participants had higher scores than males (9,21). The reason for this difference was the type of questionnaire and the age group of participants.…”
Section: Discussioncontrasting
confidence: 41%
“…Jabarifar at el. showed that the Persian version of the F-ECOHIS questionnaire was valid and reliable for assessing the oral health-related quality of life OHRQoL of preschool children of Farsi-speaking parents (9). Examination of each child on a chair with head light was performed by a trained dentist using a disposable dental mirror and a probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity and reliability of Iranian version of questionnaires have been evaluated previously [11][12][13] Due to variability of age groups, different types of questionnaires were used: Early Childhood Oral Health Impact Scale (ECOHIS) was chosen for children 2-7 years old [11]; Child Perception Questionnaire (CPQ) was applied to 8-10-year olds [12] and Child Oral Impact Daily Performance (Child-OIPD) for ages 11-15 [13]. ECOHIS and CPQ are 5-point Likert scales with options from 0 = never to 4 = every day/almost every day.…”
Section: Subjectsmentioning
confidence: 99%
“…La ECOHIS ha sido validada en numerosos países, entre ellos Argentina, Venezuela y recientemente Perú (5) . Además ha sido traducido al Francés (6) , Chino (7) , Farsi (8) , Turco (9) , Portugués Brasileño (10,11) , Español (12) , Lituano (13) , Malasio (14) y Árabe (15) . Es así, como realizar la aplicación de la encuesta ECOHIS en Chile, va a permitir analizar el impacto de la salud oral en la calidad de vida y al mismo tiempo comparar la realidad de la población Chilena con poblaciones de otros países.…”
Section: Introductionunclassified